Evaluating smile aesthetic satisfaction and related smile characteristics in dental students - Vy Thi Nhat Nguyen; Nhu-Ngoc Thi Tran; Nghia-Huu Nguyen; Thuy-Duong Thi Nguyen (Journal of Oral Biology and Craniofacial Research)
Aim: This study aimed to assess the association between self-rated smile satisfaction and the smile dimensions among dental students. Method: An analytical cross-sectional study was conducted on 216 Vietnamese dental students. A standardized photograph was taken of each student with their frontal social smiles to assess aesthetic dimensions. A single-session self-administered questionnaire containing five questions about smile aesthetic satisfaction related to various aspects was administered to all students. Differences in smile characteristics and satisfaction scores between the two genders were evaluated. The impact of smile characteristics on satisfaction scores was assessed using multiple linear regression models. Results: Most dental students had a high smile line, parallel smile arcs, an upward upper lip curvature, a non-touching labiodental relationship, a dental midline that coincided with the midline of the face, and eight teeth displayed during smile. Most participants were satisfied with their smiles, and the self-rated satisfaction score was 67 out of 100. Self-perceived overall smile satisfaction was associated with the ''smile arc”, the ''upper lip curvature”, the ''number of teeth displayed during smile”, and the ''dental midline”. Female students had a statistically significant correlation between self-perception and smile characteristics, such as upper lip curvature, dental midline shift, and smile line. Conclusions: The smile arc, upper lip curvature, and dental midline shift affected self-perceived satisfaction among dental students. Female students showed an association between the smile parameters and self-perceived satisfaction.